Improving Grade III Students' Mathematics Learning Outcomes in Multiplication Using the Jarimatika Method - Nanda Aqidah Putri; Arini Hidayati; Lailatul Qodariyah (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
Improving students’ mastery of basic arithmetic, especially multiplication, remains an urgent issue in elementary mathematics education because many students still struggle with abstract numerical procedures that hinder their overall mathematical development. Addressing this challenge, this study aims to enhance students’ learning outcomes in multiplication through the application of the Jarimatika method in grade III of Madrasah Ibtidaiyah Nurul Mun'im. The study employs a Classroom Action Research (CAR) design implemented in two cycles, with each cycle consisting of the stages of planning, implementation, observation, and reflection. The participants were 17 grade III students at MI Nurul Mun’im. Data were collected through learning outcome tests, observations, and documentation. The findings indicate a substantial improvement in students’ achievement after the introduction of the Jarimatika method. The average score increased from 58 on the pre-test to 74 on the post-test of Cycle I, and further improved to 89 in the post-test of Cycle II. The percentage of students achieving mastery also rose from 29% to 59% and ultimately reached 100%. These results demonstrate that the Jarimatika method is effective in significantly improving students’ multiplication skills and can serve as a practical alternative strategy for strengthening foundational numeracy in elementary schools.